(untitled) (Revista Educação, Artes e Inclusão, 2022)
This article reveals the reflections and results of a master’s research carried out in 2017 regarding didactics applied to the human and musical education of Young people from the Guanacés district, in the city of Cascavel - Ceará, members of a Music Band maintained by the Society Assistance and Rural Education - SAERG. The Guanacés Band became relevant as a research proposal for promoting, through its conductor, actions that allow them to resist time and difficulties, transforming the lives of many Young people and their families with the teaching of music. The objective of the research was to know and analyze the didactic-pedagogical strategies of the conductor, in na ethnographic case study through a qualitative approach. We used the studies by Paulo Freire (2003, 2015) and Vygotsky (1999, 2001), to address the social knowledge built in the rural area and the principle of dialogicity defended as na instrument of freedom for the subjects. The research results showed that the didactic work promoted by the conductor contributes significantly to the human and musical ormation of the members of the Banda de Guanacés and plays a fundamental role in the individual and collective transformation of the socio-educational context.